A reproducible low temperature chemical solution deposition of non-polar [112̄0] and [101̄0] ZnO films for optoelectronic applications. Issue 35 (11th August 2016) - Qi, Lin; Shahzad, M. Babar; Qi, Yang
Abstract : ZnO non-polar a -plane (112̄0) and m -plane (101̄0) films are grown at Si (100) substrates by low temperature chemical bath deposition. Abstract : ZnO films with non-polar a -plane (112̄0) and m -plane (101̄0) orientations are fabricated on Si (100) substrates by low temperature chemical solution deposition. This distinctive growth is achieved by a co-effect of the seed layer templates and CBD solution. The growth mechanism is illustrated in detail and these non-polar ZnO/Si heterostructures show an excellent unidirectional conductivity which is comparable with other one-dimensional ZnO heterostructures.